Síntese de derivados de selenofenos e 4H-selenocromeno via reações de ciclização eletrofílica - Casola, Kamila Kayser (2019)
This work reports the synthesis of a series of selenium heterocyclics containing in it’s core structure. These compounds are obtained through intramolecular electrophilic cyclization reactions of alkynyl substrates and promoted by different electrophilic sources. In the first step, new alternative methods were developed to promote the intramolecular electrophilic cyclization reaction of 2-(selenobutyl)-1- (alkynyl)cyclohexanol in the presence of different electrophilic source. The use of resulted in molecular iodine series of 3-iodoselenofenes (22 examples) in yields 30 to 94% isolated yields. The use of cupper (II) bromide as an electrophilic afforded 10 examples of 3-bromoselenofenes in 50 and 94% yield. When a copper iodide and diphenyl diselenide were employed, 6 novel examples of 3- (phenylselenyl)selenophene were obtained in satisfactory to good yields (29-70%). In addition, we also successfully applied 3-iodoselenophen as a substrate in coupling conditions of the Sonogashira, Suzuki and Ulmmann type, providing the corresponding products in moderate to good (60-84%). In a second step, we developed an alternative method in the regioselective cyclization 6-endo-dig of 2-(2- (selenobutyl)aryl)-4-arylbut-3-yn-2-ol, by employing iron (III) chloride and differently substituted diorganoyl diselenides as promoters for this process. Through this cyclization protocol we obtained a series of (27 examples) 4-methylene-3- (selenoaryl)-4H-selenocromene in 30 to 71% yield. Finally, when the PhSeBr was applied to electrophilic source for 2-(2-(selenobutyl)aryl)-4-arylbut-3-in-2-ol, interestingly two examples of 3- (bromomethyl) benzo[b]selenoar-2-yl)arylmethanone were obtained in satisfactory yields.